MANAJEMEN SEKOLAH RAMAH ANAK - Moh. Dwi Kurniyawan; Sultoni Sultoni; Asep Sunandar (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstrak:The purpose of the publication of this article is to describe the management of child-friendly schools in SMPN 10 Malang starting at the planning, organizing, implementing, monitoring, and roles of school principals, teachers, parents, and outsiders towards child-friendly school programs. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of research conducted at the planning stage are to make indicators of the implementation of child-friendly schools that are listed in eight national education standards. The organizing stage is forming a child-friendly school implementation team. At the implementation stage is learning activities outside the classroom as a form of child-friendly learning. Child-friendly school supervision is conducted regularly by teachers and school principals on all school activities. Principals play a role in setting up child-friendly school programs, teachers play a role in fostering and assisting child-friendly school programs, parents play a role in supporting and participating in child-friendly school activities, and outsiders play a role in socializing child-friendly schools.Keywords: management, school, child friendly schoolAbstrak: Tujuan dari publikasi artikel ini yaitu mendeskripsikan mengenai manajemen sekolah ramah anak di SMPN 10 Malang yang dimulai pada tahap perencanaan, pengorganisasian, pelaksanaan, pengawasan, dan peran kepala sekolah, guru, orang tua, dan pihak luar terhadap program sekolah ramah anak. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil dari penelitian yang dilakukan pada tahap perencanaan adalah membuat indikator implementasi sekolah ramah anak yang tertera di dalam delapan standar nasional pendidikan. Tahap pengorganisasian yaitu membentuk tim pelaksana sekolah ramah anak. Pada Tahap pelaksanaan adalah kegiatan belajar di luar kelas sebagai bentuk pembelajaran ramah anak. Pengawasan sekolah ramah anak dilakukan secara berkala oleh guru dan kepala sekolah terhadap semua kegiatan sekolah. Kepala sekolah berperan membuat tatanan program sekolah ramah anak, guru berperan membina dan mendampingi program sekolah ramah anak, orang tua berperan mendukung dan mengikuti kegiatan sekolah ramah anak, dan pihak luar berperan member sosialisasi terkait sekolah ramah anak.Kata kunci: manajemen, sekolah, sekolah ramah anak